(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Delivering a potential drug is a predominant challenge in medicinal chemistry.in this study, bio organic compounds of Cymbopogon citratus was screened by analysing physiochemical properties like solubility, permeability, efficacy, toxicity, and metabolic stability. The optimization of drug potential against virulent protein was calculated by using docking algorithm Autodock 4.2.3. Structure based ligand docking reveals that the compounds having better inhibition potential against virulent enzymes with insoluble and impermeable activities. The organic compounds of Cymbopogon citratus were screened using Lipinski rule of five and ADME/T prediction for drug likeliness. The structure based ligand docking was done between bioactive compounds of plant and virulent protein that cause diseases. The interaction was visualized using Discovery studio and was studies. The molecular docking of bioactive compounds resulted in better inhibition potential with controlled lipophilicity level, without causing toxicity that harms the natural habitat of humans. The compounds, 1,3,4-trimethyl -3cyclohexene-1-carboxaldehyde exhibit binding energy -4.70 Kcal/mol followed by β-myrcene – 4.35 Kcal/mol and Geraniol -4.35 Kcal/mol. Hence, structure based ligand docking and in silico ADME/T studies revealed that the compounds have better inhibition potential against Apolipoprotein by improving the prediction of drug compounds.